Submarine Power Cables and the Marine Environment. Legal obligations of the Coastal States in the North-East Atlantic - Stefán Erlendsson 1965- (2016)
Submarine Cables have been laid on the seabed since the nineteenth century and have special status according to international law, which provides for the right of all states to lay cables and pipelines on the seabed. Only recently, due to increased number of cables and the cumulative impact adding to other offshore activities, awareness is raised in relation to the impact on the marine environment, which to some extent is not fully understood by scientists. Interconnection of electricity markets and the increase in use of renewable energy sources, such as wind and currents, with offshore power generation, is promoting submarine power cables as important energy infrastructure, in addition to the better known role of carrying telecommunications. This thesis describes the international obligations of the coastal states, in relation to submarine power cable projects, and operation of those in marine areas where coastal states exercise jurisdiction. The main focus is on the protection of the marine environment, while taking into account the importance and special status of such cables. The potential impact is considered and to what extent there may be obligations assess, prevent, manage or mitigate such impact. These obligations are found in the general principles of international law, and in international agreements. Further, the obligations as stipulated in EU law are highlighted, and special attention paid to the approach of the two EFTA states, Iceland and Norway, parties to the EEA Agreement. Focus is set on the planning and permitting requirements for cable projects, to show how well they serve to fulfil the international obligations, using Iceland as an example of national implementation.